Neutron Diffraction of Zirconia-Dispersed Alumina with increasing stress and temperature - Carter, Geoffrey; Van Riessen, Arie (BLACKWELL PUBLISHING, 2008)
Neutron and X-ray diffraction were used to investigate changesin the phase composition and lattice parameters with temperatureand pressure of a 20-wt% zirconia-dispersed alumina composite.Neutron diffraction was used to determine the variationof tetragonal/monoclinic zirconia phase abundance for the bulkwith stress. The bulk tetragonal/monoclinic ratio decreased by40% for a stress of 550 MPa. A difference in the tetragonal/monoclinic ratio between the near-surface and the bulk of theprocessed samples is believed to contribute to observed variationsin nonuniform strain in the matrix, which has the effect ofprestressing the sample. Placing a stress on the sample initiallyreleases this prestressing.